Novel virulence factor Cba induces antibody-dependent enhancement (ADE) of Streptococcus suis Serotype 9 infection in a mouse model - Yang, Pengjiang; Yang, Lei; Cao, Kun; Hu, Qian; Hu, Yuli; Shi, Jun; Zhao, Dun; Yu, Xinglong (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus suis (SS) is a zoonotic pathogen that affects the health of humans and the development of the pig industry. The SS Cba protein is a collagen adhesin, and a few of its homologs are related to the enhancement of bacterial adhesion. We compared the phenotypes of SS9-P10, SS9-P10 cba knockout strains and its complementary strains in vitro and in vivo and found that knocking out the cba gene did not affect the growth characteristics of the strain, but it significantly reduced the ability of SS to form biofilms, adhesion to host cells, phagocytic resistance to macrophages and attenuated virulence in a mouse infection model. These results indicated that Cba was a virulence related factor of SS9. In addition, Mice immunized with the Cba protein had higher mortality and more serious organ lesions after challenge, and the same was observed in passive immunization experiments. This phenomenon is similar to the antibody-dependent enhancement of infection by bacteria such as Acinetobacter baumannii and Streptococcus pneumoniae. To our knowledge, this is the first demonstration of antibody-dependent enhancement of SS, and these observations highlight the complexity of antibody-based therapy for SS infection.